2019
DOI: 10.3390/toxins11020065
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Based Fluorometric Ochratoxin A Assay Based on Photoinduced Electron Transfer

Abstract: This study describes a novel quencher-free fluorescent method for ochratoxin A (OTA) detection based on the photoinduced electron transfer (PIET) between guanine and fluorophore. In the absence of OTA, carboxyfluorescein (FAM)-labeled aptamer can partly hybridize with the complementary strand of OTA aptamer (OTA-cAPT), which contains four guanines at its 3′-end. As a result, the fluorescence of FAM is quenched due to PIET and stacked guanines. In the presence of OTA, FAM-labeled OTA aptamer can bind specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The results showed that the hybridization of the complementary strands destroyed the structure of the G-quadruplex ( Figure S4 ), resulting in the inhibition of fluorescence-quenching. A previous study depicted an aptasensor utilizing guanines as a quencher based on PIET [ 22 ]. However, the quencher is different from the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the hybridization of the complementary strands destroyed the structure of the G-quadruplex ( Figure S4 ), resulting in the inhibition of fluorescence-quenching. A previous study depicted an aptasensor utilizing guanines as a quencher based on PIET [ 22 ]. However, the quencher is different from the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Super G™ Blocking Buffer was purchased from GRACE BIO-LABS Inc. (Bend, OR, USA). OTA aptamer 5 -biotin-GATCGGGTGTGGGTGG CGTAAAGGGAGCATCGGACA-Cy3-3 and the complementary strand 5 -BHQ2-TGTCCG ATGC-3 [28] were synthesized in bio basic Inc. (Amherst, NY, USA). Streptavidin was diluted with PBS buffer, and then 500 picoliters of the sample was printed onto an epoxycoated slide with a microarray printing robot (sciFLEXARRAYER S3; Scienion) at 25 • C in an atmosphere of 60% humidity, as described previously [29].…”
Section: Chemicals Reagents and Instrumentsmentioning
confidence: 99%
“…Second, highly stable aptamers with prominent target diversity can be easily synthesized at low cost. Owing to these outstanding merits, several aptamer-based methods for OTA determination have been developed, such as electrochemistry- [24,25], fluorescence- [26,27], and colorimetry-based assays [28,29]. The first OTA aptamer synthesized by Cruz-Aguado for OTA detection was reported in 2008 and this aptamer has been widely used in the construction of many biosensors [30].…”
Section: Introductionmentioning
confidence: 99%